Travellers' recommender system / Nor Ashikhin Hashim - Hashim, Nor Ashikhin (2005)
The rapid growth of technology has enabled the creation of Internet as a medium of searching any information. However, internet provides information that not exactly as what was acquired by users. It also happens when user needs the information about accommodation at Kuala Lumpur. The aim of the project is to develop a prototype that help user to obtain the information of Kuala Lumpur's hotels and recommend the selected hotels based on their preferences. Travellers' Recommender System will helps user in obtaining the recommendation needed without wasting their time and money. This system uses the characteristic of agents to retrieve the data fi-om database. Each preference will ask the user to fill in important interest about their dream hotel according to their preference. Then, the result for this system is the recommendation of hotels based on user interests.